Fixed points of hesitant fuzzy set-valued maps with applications - Shagari, M.S.; Azam, A. (Carpathian Mathematical Publications, 2021)
In this paper, the notion of hesitant fuzzy fixed points is introduced. To this end, we define Suzuki-type (α,β)-weak contractions in the framework of hesitant fuzzy set-valued maps, thereby establishing some corresponding fixed point theorems. The presented concept herein is an extension of fuzzy set-valued and multi-valued mappings in the corresponding literature. Examples are provided to support the assertions and generality of our obtained ideas. Moreover, one of our results is applied to investigate sufficient conditions for existence of a class of functional equation arising in dynamic programming.